Genetic stability of live attenuated vaccines against potentially pandemic influenza viruses. Issue 49 (8th December 2015) - Kiseleva, Irina; Dubrovina, Irina; Fedorova, Ekaterina; Larionova, Natalie; Isakova–Sivak, Irina; Bazhenova, Ekaterina; Pisareva, Maria; Kuznetsova, Victoria; Flores, Jorge; Rudenko, Larisa
Highlights: H5N2, H7N3, H2N2 potentially pandemic LAIV viruses were detected in vaccines. We studied genetic stability of potentially pandemic LAIVs clinical isolates. All LAIVs tested displayed high genetic stability of attenuating mutations. No viral RNA was found in any of the placebo recipients after vaccination. Abstract: Background: Ensuring genetic stability is a prerequisite for live attenuated influenza vaccine (LAIV). This study describes the results of virus shedding and clinical isolates' testing of Phase I clinical trials of Russian LAIVs against potentially pandemic influenza viruses in healthy adults. Methods: Three live attenuated vaccines against potentially pandemic influenza viruses, H2N2 LAIV, H5N2 LAIV and H7N3 LAIV, generated by classical reassortment in eggs, were studied. For each vaccine tested, subjects were randomly distributed into two groups to receive two doses of either LAIV or placebo at a 3:1 vaccine/placebo ratio. Nasal swabs were examined for vaccine virus shedding by culturing in eggs and by PCR. Vaccine isolates were tested for temperature sensitivity and cold-adaptation ( ts/ca phenotypes) and for nucleotide sequence. Results: The majority of nasal wash positive specimens were detected on the first day following vaccination. PCR method demonstrated higher sensitivity than routine virus isolation in eggs. None of the placebo recipients had detectable vaccine virus replication. All viruses isolated from the immunized subjects retained the ts/ca phenotypic characteristics of the master donor virus (MDV) and were shown to preserve all attenuating mutations described for the MDV. These data suggest high level of vaccine virus genetic stability after replication in humans. During manufacture process, no additional mutations occurred in the genome of H2N2 LAIV. In contrast, one amino acid change in the HA of H7N3 LAIV and two additional mutations in the HA of H5N2 LAIV manufactured vaccine lot were detected, however, they did not affect their ts/ca phenotypes. Conclusions: Our clinical trials revealed phenotypic and genetic stability of the LAIV viruses recovered from the immunized volunteers. In addition, no vaccine virus was detected in the placebo groups indicating the lack of person-to-person transmission. LAIV TRIAL REGISTRATION at ClinicalTrials.gov: H7N3-NCT01511419; H5N2-NCT01719783; H2N2-NCT01982331.